The Internet of Things (IoT) Impact on Global Security - Triwahyuni, Dewi (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this study is analyze from the perspectives political science and international relations the role of this emerging technology in global affairs, especially on the potential strategic impact of the IoT impact on Global Security. The Internet of Things (IoT) will impact every area of Global Affairs from security to business to international development and aid. As objects, data, systems and people become part of this global interconnected network, business models, stakeholder interaction, systems of governance and security threats will irrevocably change. Governments, not-for-profit organizations and business will have no choice but to innovate, optimize and incorporate an increasingly disparate array of digital touchpoints when engaging with stakeholders, assessing threats and collaborating with partners. This is not a technological problem; it is a strategic issue that has no tool or program that will solve the problems that this technology will bring. To answer the problem of research, researcher use qualitative research design. Researchers use primary sources in the form of official state documents and secondary sources in the form of interviews with experts, through journals, dissertations and related research. The results of the study found that the massive development of IoT creates information vulnerability that threatens national security as well as global security.